Pelatihan, Pendamping dan Evaluasi Peningkatan Kapasitas Masyarakat di Tingkat Kelurahan dalam Mewujudkan Lorong Sehat Makassar - Syamsuddin -; Rini Angraeni; Noer Bahry Noor; Adelia U. Ady Mangilep; Sukri Palutturi (Faculty of Engineering UNHAS, 2019)
Lorong Sehat (Longset) is one of the innovation programs to realize the improvement of the lives of healthy citizens of Makassar City. This program is specifically aimed at increasing public awareness to protect the environment and clean and healthy living behavior, from providing socialization to program evaluation to community members, one of which is to teach healthy life, wash hands before eating, get used to checking babies/toddlers to posyandu if there is , dispose of garbage in its place, and so on so that basic health can be fulfilled. This program is also contained in the Makassar City Medium-Term Development Plan (RPJMD) document for the 2014-2019 period. This service is a response to the existence of several problems that focus on the problems mostly in the periphery (slum area) which in this case is dominated by people living in 7000 aisles/alleys of Makassar City who have difficulty reaching basic health data. This planning process involves the community together with the government conducted at a Planning and Development Deliberation (Musrembang) meeting and monitored directly by leaders in the Health Office, such as section heads, field heads, official secretaries and even agency heads who directly monitor through the head of the puskesmas and figures community about health problems. The immediate impact of community empowerment was that the residents in the hallway were immediately handled by the people who had been given training and direct coordination by the puskesmas. Based on the results of the analysis on the healthy Aisle training there was an increase in participants knowledge regarding healthy aisles, Clean and Healthy Life Behavior (PHBS), Non-Smoking Areas (KTR), personal hygiene and Maternal and Child Health (MCH). With the existence of this healthy Hallway training, it is expected that the trainees can apply the knowledge they have acquired and can spread their knowledge to the people in their environment so that they can help the development process of the healthy Hallway.